Herpes simplex meningitis presenting as headache in pregnancy: A case report - David Boedeker; Angela Shaddeau (Case Reports in Women's Health, 2022)
Background: There are few case reports of meningitis caused by herpes simplex virus (HSV) as the initial presentation in a pregnant patient, making pregnancy management and delivery planning challenging for obstetricians encountering this patient presentation. Case: A 35-year-old parous woman at 35 weeks of gestation with prenatal care complicated by her history of pre-term delivery and systemic lupus erythematous (SLE) presented to the emergency department with worsening headache not responding to medication. Due to her history of SLE, rheumatology was consulted, although her flare symptoms were not consistent with her initial presentation. Neurology was consulted after she developed symptoms consistent with meningitis. She was started on broad-spectrum antibiotics while awaiting lumbar puncture results. The latter indicated the patient was positive for HSV-2 IgG, suggesting a recurrent process. She denied a personal history of HSV infection, although she had a positive unspecified HSV IgM titer upon chart review. The patient was transitioned to intravenous acyclovir and responded well. Upon clinical improvement, she was transitioned to oral antiviral therapy and subsequently discharged home. After consultation with the pediatrics and pediatric infectious disease departments, vaginal delivery was deemed to be safe. However, the patient elected for primary cesarean. Conclusions: Providers encountering a patient with an unrelenting headache in the absence of other causes should have a high suspicion for meningitis, regardless of clinical HSV history.